Analogies, Metaphors, and Similes for HIV/AIDS Among Ugandan Grade 11 Students (Alberta Journal of Educational Research, 2007)
This article looks at the importance of student-generated analogies, metaphors, and similes as an entry point into their understandings of HIV/AIDS. In addition, it argues that analogies, metaphors, and similes are good tools for eliciting students’ prior understandings of HIV/AIDS, especially matters relating to sexuality that are often figuratively communicated in many Ugandan cultures. It posits that students’ prior knowledge determines how they respond to messages about HIV/AIDS. The article suggests that in order to prevent vulnerability to HIV/AIDS among Ugandan youth, learning should be viewed as a process of conceptual change so that students become active participants in their own learning process.